Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s00234-016-1737-3
|View full text |Cite
|
Sign up to set email alerts
|

Basic MR sequence parameters systematically bias automated brain volume estimation

Abstract: SynopsisStandard MR parameters, notably spatial resolution, contrast and image filtering, systematically bias results of automated brain MRI morphometry by up to 4.8%. This is in the same range as early disease-related brain volume alterations, for example in Alzheimer's disease. Automated brain segmentation software packages should therefore require strict MR parameter selection or include compensatory algorithms to avoid MR-parameter-related bias of brain morphometry results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…However, the agreement in terms of absolute volumes varies with acquisition protocols and field strength. For example, change in voxel size can lead to systematic errors in the range of 5% for hippocampal volume [ 181 ]. Methods to correct for these variabilities are being investigated [ 86 ].…”
Section: Imaging As An Outcome Measure In Trialsmentioning
confidence: 99%
“…However, the agreement in terms of absolute volumes varies with acquisition protocols and field strength. For example, change in voxel size can lead to systematic errors in the range of 5% for hippocampal volume [ 181 ]. Methods to correct for these variabilities are being investigated [ 86 ].…”
Section: Imaging As An Outcome Measure In Trialsmentioning
confidence: 99%
“…Finally, recent work ( Haller et al, 2016 ) has shown that protocol specific MR parameters can systematically bias the results of automated volume estimation of a number of brain structures by 4–5%. We must therefore consider the possibility of a similar effect could being present when estimating lesion volume.…”
Section: Resultsmentioning
confidence: 99%
“…10,11 Voxel-based morphometry has been used successfully to investigate a wide number of disorders such as Alzheimer's disease (AD), 12 Parkinson's disease, 13 depression, 14 and multiple sclerosis. 15 Clinical application of these methods would appear promising in the assessment of neurodegenerative conditions; automated brain morphometry is increasingly recognized as a biomarker for AD 16 and atrophy measurement from serial scans is an attractive way to characterize diseases such as multiple sclerosis. 17,18 However, while a number of these sophisticated methods of analysis are available to quantify local and global atrophy from MRI, relatively little progress has been made to integrate these into clinical workflows due to special hardware requirements, prohibitively long processing times and dependency on specific acquisition techniques.…”
Section: Introductionmentioning
confidence: 99%